Synthetic fixative in perfume formulation: evaluating longevity, stability, and cost - Manikkam, M. Abarnah; Keng, Chia Ming; Lee, Wei Hao; Thayalan@Barathi, Previin; Nurul Akmarina, Mohd Abdul Kamal; Azlina, Ahmad; Afiq, Azil (Zenodo, 2025)
This study was conducted to evaluate the effects of fixative on fragrance longevity, pH stability, formulation stability, and cost-effectiveness in perfume formulation. The comparison Ambroxane (synthetic fixative) and a control sample without fixative aimed to determine its role in enhancing perfume performance while maintaining formulation integrity. Experimental analyses included evaporation rate testing, pH measurement, stability assessment, and cost evaluation. The evaporation rate test measured fragrance longevity, while pH analysis was conducted using pH strips and a digital pH meter. Stability testing assessed the physical integrity of formulations under room temperature (27°C), high temperature (50°C), and low temperature (4°C) over 14 days. The cost analysis compared the economic feasibility of Ambroxane in large-scale production. The evaporation rate test showed that Ambroxane had a slower evaporation rate at 0.010 mg/hour, while the control sample evaporated the fastest at 0.017 mg/hour. pH analysis revealed that Ambroxane resulted in a lower pH (7.04), followed by the Control (7.11), with statistical significance confirmed (p < 0.05). Stability testing confirmed that both formulations remained clear and homogeneous across all conditions, with no visible phase separation or discoloration. Cost analysis indicated that the Ambroxane formulation (RM 6.61 per 50 mL) was cheaper compared to the control formulation (RM 7.41 per 50 mL). The findings confirm that fixative significantly impacts fragrance longevity, stability, and cost. Ambroxane provided superior longevity and cost-effectiveness, making it suitable for large-scale production, with minimal impact on stability and pH. This study successfully met its objective by providing a comprehensive comparison of fixative material, offering valuable insights for perfumers and manufacturers in selecting Ambroxane as an optimal fixative based on market positioning, cost constraints, and fragrance performance requirements.